It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social

Mon corps a-t-il un sexe? Sur le genre, dialogues entre biologies et sciences sociales - Gonthier, Josiane; Ruppli-Coursange, Mireille (Recherches (Paris. 1994), 2015)
"Sexe" est l'un des mots de la langue française que les gens sans distinction de classe, de religion, d'apparence ou de profession, utilisent avec grand intérêt, qu'ils soient accoudés au zinc d'un bistrot ou à la paillasse d'un laboratoire de biologie moléculaire. Deux mises en scène distinctes, sociale ou scientifique ; deux scénarios différents : d'un côté, les histoires d'amour ou d'imaginaire sexuel, de l'autre, les recherches biologiques. Sous ce mot de "sexe", notre langue, si riche, produit une polysémie bien fâcheuse. L'ambition de ce volume, qui rassemble les contributions de chercheurs et chercheuses en sciences de la vie et en sciences humaines et sociales est de faire le point sur les connaissances concernant le sexe biologique et ses variations, dont on sait désormais qu'il ne permet pas de séparer les individus en deux catégories bien distinctes. Ce livre veut aussi évaluer l'impact du genre sur le développement du corps des êtres sexués et sur la construction de leur identité. Enfin, il cherche à apprécier dans quelle mesure les croyances liées au genre (bicatégorisation mâle-femelle stricte, supériorité masculine) ont pu influencer les recherches menées sur le sexe biologique. Et les témoignages de personnes intersexes et transgenres apportent sur la question de l'identité sexuée un éclairage complémentaire qui bouscule les "réponses" que donnent le plus souvent la médecine et le droit.
Keywords: approches et analyses; biologie; corps; cours; discipline; discours dominant; premier cycle; psy4910; psychologie; pédagogie; queer; sciences; sciences humaines; sciences sociales; sexualité; systèmes d'oppressions; thématiques; épistémologie; études de genres

"Why Should Our Bodies End at the Skin?": Embodiment, Boundaries, and Somatechnics - SHILDRICK, MARGRIT (Hypatia, 2015)
Donna Haraway's enduring question—"Why should our bodies end at the skin?" (Haraway 1990, 220)—is ever more relevant in the postmodern era, where issues of bodies, boundaries, and technologies increasingly challenge not only the normative performance of the human subject, but also the very understanding of what counts as human. Critical Disability Studies has taken up the problematic of technology, particularly in relation to the deployment of prostheses by people with disabilities. Yet rehabilitation to normative practice or appearance is no longer the point; instead, the lived experience of disability generates its own specific possibilities that both limit and extend the performativity of the embodied self. I look at what is at stake in the challenge to the Western logos that comes specifically from the capacities of the disabled body, understood not as a less than perfect form of the normative, but as figuring difference in a nonbinary sense. Feminist theory has long contested the isomorphism of the logos, but I go beyond simply setting out the grounds for revaluing multiple variant forms. The feminist turn to Jacques Derrida and Gilles Deleuze opens up the problematic to a celebratory positioning of difference and transcorporeality as the very conditions of life.
Keywords: EDI; approches et analyses; arts; bioéthique; corps; cours; discipline; philosophie; postmodernisme; premier cycle; prothèses; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; technologie; thématiques; études critiques du handicap; études littéraires